153k views
3 votes
Can someone please solve this and explain the steps?

Can someone please solve this and explain the steps?-example-1

2 Answers

1 vote

Answer: -45

Explanation:

You start off by plugging in -10 for the the x in 4(x)

You do this because h(x)=4x therefore if the x in h(x) is -10, so is the x in 4(x)

By plugging it in you would get 4(-10) thats -40

then you put -40 in the g equation

if g(x)= x-5 and x=-40

you would end up with g(x)=(-40)-5 which is -45!

User PleaseStand
by
4.7k points
1 vote
Answer:

-45

Steps:

First, plug -10 in for x in h(x);

h(-10) = 4 * -10

h(-10) = -40

Then, plug this result (-40) in for the x in g(x);

g(-40) = -40 - 5

g(-40) = -45
User Gooly
by
5.0k points